Conservation Of The Rufous-Collared Kingfisher (Actenoides Concretus) Protected By Implementing The Enrichment Planting Method In Labuhan Ix Village - Syarief, Ayu Nirmala Lutfie; Pamungkas, Bayu Aji; Prasetyo, Catur Yogi; Putri, Rinda Aryani (Green Publisher Indonesia, 2025)
This research aims to protect the endangered Rufous-Collared Kingfisher (Actenoides concretus) and restore the habitat of this protected bird. This research was conducted at the Plang Ijo Cooperative, a non-governmental organization. The survey location was Labuhan Ratu IX Village, East Lampung Regency, Lampung Province. The research method used was the Shannon-Wiener method. The results of this study indicate that the program's contribution to the environment and/or community includes the ecology of Way Kambas National Park, public education, and economic improvement. Prior to the program, Rufous-Collared Kingfisher (Actenoides Concretus) species was not found, habitat loss occurred, and public aware ness was low. After the program, rejuvenation of the swamp area around Labuhan Ratu IX Village was carried out in collaboration with the Plang Ijo Cooperative as an effort to restore the natural ecosystem of the habitat using enrichment planting (genome-based ecosystem restoration classification using ecological engineering techniques). The program's contribution to achieving the SDGs includes addressing climate change and terrestrial ecosystems.